فعالية استخدام لعبة Domino في إتقان المفردات لطلاب في مدرسة ثانوية المدينة ديوك جومبانج - Dewi Rohmawati; Muhammad Arif Setyabudi Arif Setyabudi (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
The importance of the Arabic language is not limited to being the language of religion; it also plays a significant role in the development of science. However, in practice, teaching Arabic in schools still faces various challenges, including students’ low interest and the use of less engaging teaching methods. This study aims to measure the effectiveness of the domino mufrodat method in improving Arabic vocabulary mastery among tenth-grade students at Al-Madinah Senior High School Diwek Jombang. The background of this study is based on the low effectiveness of traditional teaching methods, which generally rely only on writing vocabulary on the board. The research questions are: (1) How is the domino game used at Al-Madinah Senior High School Diwek Jombang? (2) How effective is the use of the domino game in mastering vocabulary for students at the school? This study used a quantitative approach with a one-group pretest-posttest experimental design. The research sample consisted of tenth-grade students who were given a pretest, followed by treatment using domino mufrodat media, and a posttest afterward. Data collection techniques included observation, interviews, tests, and documentation. The results of this study can be summarized as follows: (1) The use of domino mufrodat in classroom learning involved several stages, including dividing students into small groups, the teacher explaining the game rules, students playing the game, and the teacher moving around to guide and ensure active participation. After the game ended, there was a reflection session with questions and answers. (2) The average posttest score was higher than the pretest, indicating an improvement in learning outcomes after using the domino mufrodat media. The normality test showed that the data were normally distributed (pretest significance 0.184; posttest 0.089 > 0.05). The paired t-test showed a significant difference (significance 0.000 < 0.05). The N-Gain score of 0.6893 indicates that the method's effectiveness is in the medium to high category. Based on these results, it can be concluded that using domino mufrodat media is effective in improving students’ vocabulary mastery and creating a more active, engaging, and interactive learning atmosphere. This media can also help overcome the assumption that Arabic is a difficult subject